2015
DOI: 10.1002/pon.3834
|View full text |Cite
|
Sign up to set email alerts
|

Resilience as a predictor for emotional response to the diagnosis and surgery in breast cancer patients

Abstract: Our results confirm that resilience may at least partially protect against emotional distress in cancer patients. Our findings suggest that resilience may be a relatively stable trait that is not affected by adversity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

13
84
1
8

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 88 publications
(106 citation statements)
references
References 46 publications
13
84
1
8
Order By: Relevance
“…The novel contribution from this study is that the relationship between resilience and distress was mediated by difficulties in emotion regulation. These results aligned with previous research findings that resilience was negatively correlated with distress …”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…The novel contribution from this study is that the relationship between resilience and distress was mediated by difficulties in emotion regulation. These results aligned with previous research findings that resilience was negatively correlated with distress …”
Section: Discussionsupporting
confidence: 92%
“…Second, participants' transient mood states may have amplified their potential recall bias, such that if people were experiencing acute distress at the time of completing the questionnaire (eg, they may have received bad scan results that week), this may have affected their subsequent responses. However, in a study of women with breast cancer compared against healthy female controls, resilience did not differ significantly between the two groups . While cancer patients reported higher levels of anxiety, depression, and negative effect, higher levels of resilience were associated with better emotional adjustment with both women with cancer and in control women.…”
Section: Discussionmentioning
confidence: 87%
See 1 more Smart Citation
“…According to significant role of these strategies in predicting resiliency in chronic diseases, surprisingly no research is found in relation to the aforementioned parameters in advanced cancer specifically stage IV (end of life). In addition, despite the huge portion of resiliency in psychological well-being of this group, we found that a few investigations dedicated to this mediator (8,30,31).…”
Section: Introductionmentioning
confidence: 78%
“…These adaptive traits help to replenish emotional resources, relieve potential suffering, and enhance positive coping methods [41]. Studies of individuals with cancer have suggested that resilience provides at least partial protection against emotional distress, leading to better emotional adjustment [42]. Other studies have indicated that aspects of hope and resilience, such as positive expectations and optimism, have predicted better health outcomes after heart transplantation and coronary bypass surgery [43-44].…”
Section: Reviewmentioning
confidence: 99%